Podstarościowie i pisarze grodzcy w świecie wielkiej i małej polityki (na przykładzie urzędników grodzkich województwa sandomierskiego w XVII wieku) - Pielas, Jacek (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The article is devoted to the issue of the participation of the most important town officials – sub-elders and courts writers – in politics at the level of noble self-government as well as the parliament and central institutions of the noble state on the example of the officials of the strongholds of the Sandomierz province in the 17th century. The article presents the results of many years of source search, allowing to present the staffing of the above-mentioned offices in seven strongholds of the former Sandomierz region in the 17th century and to evaluate the involvement of those in these offices in small and large politics. The article presents typical manifestations of the involvement of these officials in public life, as well as spectacular careers and political activity of the most prominent representatives of this clerical group from the Sandomierz province.